(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Global biodiversity initiatives must prioritize plant conservation, but Indigenous groups, who have long maintained symbiotic links with their local surroundings, sometimes, have their opinions ignored. This study examines Indigenous viewpoints on plant conservation, emphasizing the traditional ecological knowledge (TEK) these groups possess, their cultural and spiritual relationships to plants, and their environmentally friendly behaviors that support biodiversity preservation. More effective and culturally sensitive conservation outcomes may result from an understanding of and integration of Indigenous knowledge into contemporary conservation strategies.